Study on the Readiness among Youth towards Industry 4.0 - Dr. Vinita Sharma, Tanu Manocha (International Journal of Advanced Science and Technology, 2020)
The initiative of Industry 4.0 possesses a great challenge in the whole world provided with the new innovative and smart technologies in all areas of the industry, which actually leads to digital transformation. The speed and scope of digitization and development is changing very fast due to emergence of new technologies and also due to implementation of these technologies. This digitization is affecting the people, processes and thus overall society. Thus, it becomes the need of the hour to assess the readiness of the users towards industry 4.0 for the transformation and change. The aim of the paper is to explore the readiness on adoption of industry 4.0 among youth. It also identifies various factors that are required to develop the readiness to implement Industry 4.0. The study aimed to carry out a research of 87 respondents (sample size, n=87) by using random sampling approach to unfold the readiness of youth towards Industry 4.0. Statistically analysed data explored that respondents are not very well aware of industry 4.0. More awareness is to be created and youth is moving towards developing readiness towards industry 4.0. The study also explores various factors that are required to develop readiness to implement Industry 4.0 in any organisation. The factor analysis method was carried out by using SPSS software. The result indicates that technical skills and non-technical skills and both qualitative and quantitative skills are required to develop the readiness to implement Industry 4.0 in Indian scenario.